Moral distress of nurses working in paediatric healthcare settings - Miranda, Ana Cristina Ribeiro (2024)
This scoping review aims to map the evidence on moral distress of nurses working in paediatric healthcare settings from homecare to hospital. It was conducted according to the Joanna Briggs Institute. International databases were searched according to the specific thesaurus and free search terms. Independent screening and analysis were conducted using Rayyan QCRI. This review considered a total of 54 studies, including quantitative and qualitative studies, systematic reviews, and grey literature; English and Portuguese languages were included. Moral distress is a phenomenon discussed in nursing literature and in the paediatric context but is considered absent from discussion in clinical practice. It is caused by disproportionate care associated with overtreatment. Nurses can present a variety of symptoms, characterising moral distress as a highly subjective experience. The paediatric contexts of practice should promote a healthy ethical climate and work towards a moral community built with peer support, education, communication, leadership, and management involvement. Moral distress is still a complex and challenging multidimensional concept, and the aim should be to promote a culture of prevention of the devastating consequences of moral distress and work towards moral resilience.